Directional gravity wave momentum fluxes in the stratosphere derived from high‐resolution AIRS temperature data. Issue 1 (5th January 2017) - Ern, M.; Hoffmann, L.; Preusse, P.
Abstract: In order to reduce uncertainties in modeling the stratospheric circulation, global observations of gravity wave momentum flux (GWMF) vectors are required for comparison with distributions of resolved and parametrized GWMF in global models. For the first time, we derive GWMF vectors globally from data of a nadir‐viewing satellite instrument: we apply a 3‐D method to an Atmospheric Infrared Sounder (AIRS) temperature data set that was optimized for gravity wave (GW) analysis. For January 2009, the resulting distributions of GW amplitudes and of net GWMF highlight the importance of GWs in the polar vortex and the summertime subtropics. Net GWMF is preferentially directed opposite to the background wind, and, interestingly, it is dominated by large‐amplitude GWs of relatively long horizontal wavelength. For convective GW sources, these large horizontal scales are in contradiction with traditional thoughts. However, the observational filter effect needs to be kept in mind when interpreting the results. Key Points: A first global distribution of net gravity wave momentum flux is derived from satellite observations Net gravity wave momentum flux (net GWMF) is directed prevalently opposite to the background wind Waves of large‐amplitude and above‐average horizontal scale dominate the net GWMF distribution